The Role of Engagement in Influencing High School Students’ Future Time Perspectives: A Gender Moderation - Ridho, Ali (Universitas Negeri Malang, 2024)
This research explores the interaction between academic engagement, gender differences, and future time perspective (FTP) among high school students. The aim is to shed light on how this factor contributes to students’ orientation towards their future. This research used a survey design with a sample of 109 students to examine the prediction of academic engagement to FTP and the moderating role of gender. The findings showed a significant positive prediction of engagement to FTP, which was more pronounced in male students, highlighting the importance of gender as a moderating factor. This research emphasizes the multidimensional nature of engagement—emotional, behavioral, and cognitive—and its essential role in shaping FTP. The impact of the learning environment and teacher-student dynamics on engagement and FTP, which is nuanced by gender differences, is also explored. Based on these insights, the result recommends future research directions, including longitudinal studies, to further understand engagement and FTP developmental trajectories, explore additional moderating factors, and intervene in education supporting gender equity.